2007
DOI: 10.1016/j.jcv.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing 56 complete SARS-CoV S-gene sequences from Hong Kong

Abstract: The ML approach to the reconstruction of tree phylogenies is known to be superior to the more popular, less computationally and time-demanding neighbour-joining (NJ) approach. The ML analysis in this study confirms the previously reported SARS epidemiology analysed mostly using the NJ approach. The two new SNVs reported here are most likely due to the tissue-culture passaging of the clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…25 All SARS-CoV isolates from epidemic countries and regions outside mainland China could be traced to Guangdong or Hong Kong based on the S-gene SNV motif. 23,39 During the second sporadic outbreaks of 2003e2004, it was shown that the SARS-CoV sequences from index patients were almost identical to that from civets collected in the same period and all retained the 29-nt sequence in the ORF8 gene. The mild disease symptoms associated with these viruses and the lack of rapid human-to-human transmission provided further evidence that the rapid adaptation of the SARS-CoV in the first major outbreak of 2002e2003 was essential for its establishment and pathogenesis in humans.…”
Section: Rapid Adaptation Of Sars-covs In Humansmentioning
confidence: 99%
“…25 All SARS-CoV isolates from epidemic countries and regions outside mainland China could be traced to Guangdong or Hong Kong based on the S-gene SNV motif. 23,39 During the second sporadic outbreaks of 2003e2004, it was shown that the SARS-CoV sequences from index patients were almost identical to that from civets collected in the same period and all retained the 29-nt sequence in the ORF8 gene. The mild disease symptoms associated with these viruses and the lack of rapid human-to-human transmission provided further evidence that the rapid adaptation of the SARS-CoV in the first major outbreak of 2002e2003 was essential for its establishment and pathogenesis in humans.…”
Section: Rapid Adaptation Of Sars-covs In Humansmentioning
confidence: 99%
“…If these CR3022 binding regions are to continue to serve as epitopes without escape mutations, one would hope to see them as not differing by non-conservative mutations in early SARS isolates. For example, we would hope that SARS isolates from Hong Kong patients have similar subsequences, and they certainly are [ 36 ] when compared with the large range of the less close variants [ 4 ] and of more distant coronaviruses [ 5 ]. Nonetheless, one sees differences within those regions that would not normally be considered as conservative substitutions: serine (S) to phenylalanine (F) (small polar to large non-polar), threonine (T) to methionine (M) (small polar to large non-polar), and histidine (H) to asparagine (N) (large partially charged to small neutral polar).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenies 239,241 constructed using ML 242,243 and Bayesian methods 244 consistently distinguished the late-phase strains as a monophyletic cluster, supporting the viewpoint that the local outbreaks later in Hong Kong, as well as those in other parts of the world, were largely, if not completely, derived from a common source. In fact, the SCoV spike (S) glycoprotein gene phylogeny suggested that multiple SCoV strains might have been independently introduced into Hong Kong from Guangdong before the SSE in Hotel M, although none of these strains contributed substantially to the subsequent outbreaks.…”
Section: Molecular Epidemiology Of Sars Outbreaksmentioning
confidence: 88%